ISLAMIC EDUCATION PARADIGM ON RELIGIOUS UNDERSTANDING IN INDONESIA (A CASE STUDY AT ISLAMIC BOARDING SCHOOL OF AL-MUAYYAD SURAKARTA) - Supriyanto Supriyanto; Amrin Amrin; Andi Arif Rifa'i (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2022)
This research stems from the anxiety that Islamic boarding schools seen as Islamic educational institutions have different understandings in interpreting religious teachings, so their actualization in society is also different. Al-Muayyad Islamic Boarding School is more moderate, thus it is highlighted as an Islamic educational institution used as a breeding ground for terrorism. This research aims to determine the concept and the implications of education and religious understanding at Islamic Boarding School of Al-Muayyad Surakarta in the community. The type of this research applied descriptive qualitative method of field studies. The data collection used observation, interviews and documentation. Meanwhile, the analysis employed the interpretation of cohesion with the verstehen method. This method means an interpretation attempted to explain the observed sociological phenomena in accordance with the meaning given by the object being observed. The results indicate that the Al-Muayyad Islamic Boarding School as a traditional Islamic educational institution aims to understand and practice Islamic teachings by emphasizing moral values. The concept of Islamic education implemented by Al-Muayyad Islamic Boarding School is in the process of creating integrated values and students’ personalities. First, the commitment of Islamic education to tafaqquh fi al-din. Second, long term education. Third, the concept of integrative education. Fourth, to display the concept of Islamic education as a whole. Al-Muayyad as a salafiyah Islamic Education places Islam as a manhaj al-fikr, building an Islamic character that is tawasuth and inclusive. Aswaja as manhaj al-fikr provides a frame in the creation of Islam respecting tradition, pluralism, tolerance, democracy and other humanistic values in accordance with the concept of maqashid al-syariah which includes five basic human rights. The concept of jihad is comprehended as a form of attitude and response to existing human values, in addition to Al-Muayyad as a sub-culture of society.